2005
DOI: 10.1590/s1516-89132005000800002
|View full text |Cite
|
Sign up to set email alerts
|

Soil resistance to penetration and least limiting water range for soybean yield in a haplustox from Brazil

Abstract: The objective of this study was determine the resistance to penetration (PR), least limiting water range (LLWR) and critical bulk density (D b-crit ) for soybean yield in a medium-textured oxisol (Haplustox

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
(52 reference statements)
2
16
0
13
Order By: Relevance
“…According to Tormena et al (1999) and Beutler et al (2005), the upper limiting value of LLWR in tropical soils was θ FC and the lower limit was θ PR . The factor that reduces the range of LLWR, with compaction increasing (D b ), was θ PR , in inferior limiting up to the end of LLWR (LLWR = 0), when it reached the critical bulk density (D bc ) to soybean yield, which changed from 1.52 to 1.60 Mg m -3 , in both years (Figure 3 A )...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Tormena et al (1999) and Beutler et al (2005), the upper limiting value of LLWR in tropical soils was θ FC and the lower limit was θ PR . The factor that reduces the range of LLWR, with compaction increasing (D b ), was θ PR , in inferior limiting up to the end of LLWR (LLWR = 0), when it reached the critical bulk density (D bc ) to soybean yield, which changed from 1.52 to 1.60 Mg m -3 , in both years (Figure 3 A )...…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, decreases in yield were found until D b reached 1.60 Mg m -3 (Figure 1) equivalent to the highest D bc in LLWR (Figure 3), which indicates that the LLWR is a model that can be used to monitor soil physical quality for soybean yield, according to Beutler et al (2005). The use of D bc (LLWR = 0), as indicated in the present work, is a possible form to monitor soil compaction and establish its relations with plants, and its use as soil physical indicator, since Benjamin et al (2003) found little correlation of LLWR>0 with corn and wheat yield.…”
Section: And B)mentioning
confidence: 96%
See 1 more Smart Citation
“…A densidade do solo variou de 1,33 a 1,52 Mg m -3 , e foi inferior ao valor de 1,55 Mg m -3 , considerado limitante para culturas anuais em solos com 200 a 550 g kg -1 de argila, no Sul do Brasil (Reichert et al, 2003), e próximo de 1,48 Mg m -3 , em que Beutler et al (2005) obtiveram a máxima produtividade de soja em solo e clima semelhante. Assim, a densidade do solo não foi fator limitante da produtividade nos sistemas de manejo, indicando que o sistema de semeadura direta com utilização de plantas de cobertura em pré-safra não compacta o solo em níveis prejudiciais à produtividade de culturas anuais.…”
Section: Resultsunclassified
“…Solos mais compactados aumentam o desempenho de tração dos pneus porém requerem mais esforço para serem mobilizados, aumentam o desgaste de máquinas e equipamentos e podem prejudicar ou mesmo impedir o desenvolvimento radicular das plantas (Silva et al, 2000) e torná-las, assim, mais suscetíveis a perdas de produtividade em condições de deficiência hídrica (Beutler et al, 2005).…”
Section: Introductionunclassified